MENINGKATKAN AKTIVITAS, KETERAMPILAN KOLABORASI, DAN HASIL BELAJAR PESERTA DIDIK MENGGUNAKAN MODEL GEN PADA PEMBELAJARAN IPAS: Penelitian Tindakan Kelas - Diang Novita Wulansari; Fathul Jannah (STKIP Subang, 2024)
The problem in this study is the low activity, collaboration skills and learning outcomes of students in participating in learning. The existence of this problem was the reason for carrying out classroom action research with three meetings held by the researcher. The subjects of this research were class V students at SDN Sidomulyo 2 with a total of 22 students. The results of this study indicate that the activities of educators at meeting III obtained the criteria